2023
DOI: 10.3390/ph16091196
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Kan Jang® in Patients with Mild COVID-19: A Randomized, Quadruple-Blind, Placebo-Controlled Trial

Levan Ratiani,
Elene Pachkoria,
Nato Mamageishvili
et al.

Abstract: Background and aim. This study aimed to assess the efficacy of the treatment of Kan Jang®, a fixed combination of Andrographis paniculata (Burm. F.) Wall. ex. Nees and Eleutherococcus senticosus (Rupr. & Maxim.) Maxim extracts in patients with mild symptoms of COVID-19. Methods. One hundred and forty patients received six capsules of Kan Jang® (n = 68, daily dose of andrographolides—90 mg) or placebo (n = 72) and supportive treatment (paracetamol) for 14 consecutive days in a randomized, quadruple-blinded,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
(83 reference statements)
0
1
0
Order By: Relevance
“…However, the use of herbal medicines such as AP extract as an alternative treatment for COVID-19 patients in combination with modern medicine has been reported in many countries including Georgia, India, and Thailand. [10][11][12] In a clinical trial for the efficacy of AP during the COVID-19 outbreak in Thailand, Mahajaroensiri et al investigated inflammatory cytokine changes and metabolomics profiling after the administration of a high dose of AP extract (180 mg/day of AP1) in five COVID-19 patients, and the results showed that inflammatory cytokines related to COVID-19 infection tended to be decreased and the metabolite profile showed a decrease of inflammatory metabolites and nucleotides. 12 A retrospective cohort study also reported that AP regimens in earlystage COVID-19 patients (60 mg of AP1 per dose, three times daily for 5 days) were found to be safe and highly effective for the prevention of disease progression to moderate COVID-19 with pneumonia.…”
Section: Introductionmentioning
confidence: 99%
“…However, the use of herbal medicines such as AP extract as an alternative treatment for COVID-19 patients in combination with modern medicine has been reported in many countries including Georgia, India, and Thailand. [10][11][12] In a clinical trial for the efficacy of AP during the COVID-19 outbreak in Thailand, Mahajaroensiri et al investigated inflammatory cytokine changes and metabolomics profiling after the administration of a high dose of AP extract (180 mg/day of AP1) in five COVID-19 patients, and the results showed that inflammatory cytokines related to COVID-19 infection tended to be decreased and the metabolite profile showed a decrease of inflammatory metabolites and nucleotides. 12 A retrospective cohort study also reported that AP regimens in earlystage COVID-19 patients (60 mg of AP1 per dose, three times daily for 5 days) were found to be safe and highly effective for the prevention of disease progression to moderate COVID-19 with pneumonia.…”
Section: Introductionmentioning
confidence: 99%